2000
DOI: 10.1590/s0100-879x2000001200011
|View full text |Cite
|
Sign up to set email alerts
|

Non-neuronal cells are not the limiting factor for the low axonal regeneration in C57BL/6J mice

Abstract: Peripheral axonal regeneration was investigated in adult male mice of the C57BL/6J (C), BALB/cJ (B) and A/J (A) strains and in their F1 descendants using a predegenerated nerve transplantation model. Four types of transplants were performed: 1) isotransplants between animals of the C, B and A strains; 2) donors of the C strain and recipients of the C x B and C x A breeding; 3) donors of the B strain and recipients of the C x B breeding, and 4) donors of the A strain and recipients of the C x A breeding. Donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…The facts reported above are in line with other works dealing with various isogenic strains of mice showing variations in the regenerative capacity after crushing or sectioning of the sciatic nerve (Lainetti et al, 1995;Lu et al, 1994;Oliveira and Langone, 2000;Oliveira, 2001;Xin et al, 1990). In this sense, C57BL/6J number of regenerated axons, 2 weeks after axotomy, was one-fifth of that in A/J.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…The facts reported above are in line with other works dealing with various isogenic strains of mice showing variations in the regenerative capacity after crushing or sectioning of the sciatic nerve (Lainetti et al, 1995;Lu et al, 1994;Oliveira and Langone, 2000;Oliveira, 2001;Xin et al, 1990). In this sense, C57BL/6J number of regenerated axons, 2 weeks after axotomy, was one-fifth of that in A/J.…”
Section: Introductionsupporting
confidence: 90%
“…In a subsequent study, the genetic and biological nature of such deficiency was linked to multiple loci (Lu et al, 1994). Another relevant finding, described by Oliveira and Langone (2000) was that non-neuronal cells in the nerve, such as Schwann cells, were not the limiting factor behind the poor regenerative potencial of C57BL/6J mice, which may probably be due to the neuronal response to injury itself. However, no mechanisms have been proposed to explain such differential response to axotomy.…”
Section: Introductionmentioning
confidence: 97%
“…Also, the possible lack of trophic support results in apoptotic neuronal death, which also includes the satellite cells in the DRG. This hypothesis is in agreement with a previous report which showed that if a predegenerated nerve was grafted to the proximal stump, C57BL/ 6J regenerative performance was greatly enhanced (13). Also, if exogenous NGF is administered after sciatic nerve transection, sensory neuron death can be partially reduced (20).…”
supporting
confidence: 92%
“…Although Lu et al (11) proposed that such a defect would be a delay rather than a permanent neuronal impairment, Lainetti et al (12) observed a large percentage of sensitive neuron death four weeks after axotomy. It has been proposed that such neuronal death may be the result of a mismatch in the timing of the neuronal need for trophic substances and their production by the non-neuronal cells in the nerve (13). In this respect, apoptotic mechanisms may be involved, and may be related to the previously described loss of C57BL/6J dorsal root ganglion (DRG) neurons.…”
mentioning
confidence: 99%
“…The thickness of the myelin sheath is a direct indicator of functional recovery of the nerve because it denotes the level of physiological activity of Schwann cells. This parameter has been used in several studies to evaluate the evolution of the axonal regenerative process (Levi and Bunge 1994;Oliveira and Langone 2000;Pierucci et al 2008). G-CSF treatment reduced the thickness of the myelin sheath and the diameter of the axons in the two strains studied.…”
Section: Discussionmentioning
confidence: 99%